2015
DOI: 10.1016/j.prosdent.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam tomography assessment of the condylar position in asymptomatic and symptomatic young individuals

Abstract: The condyle-mandibular fossa relationships of these young adults were similar in the centric relationships and maximum intercuspation positions when evaluated by computed tomography. The presence or absence of temporomandibular disorder was not correlated with the condyle position in the temporomandibular joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…Similarly, many studies have concluded that the presence or absence of TMD was not correlated with condyle position in TMJ. [22,23] In this study, superior and MJS were significantly different when affected joints in comparison with normal counterparts in both genders.…”
Section: Discussionmentioning
confidence: 46%
“…Similarly, many studies have concluded that the presence or absence of TMD was not correlated with condyle position in TMJ. [22,23] In this study, superior and MJS were significantly different when affected joints in comparison with normal counterparts in both genders.…”
Section: Discussionmentioning
confidence: 46%
“…25 Lelis et al found that there were no significant differences in the condylar positions between the centric relation and the maximum intercuspation in either symptomatic or asymptomatic young adults. 26 This could be due to different accuracy of the imaging technique, different anatomy of the samples or the young age of the patients in this study (the patients did not have enough time to develop changes in the condylar position). 26 Some researchers believe that the reasons for the posterior condylar position arise from disk displacement, 13 osteoarthritis, 23 bone remodeling of the articular eminence and the condyle, 27 and osteoarthrosis.…”
Section: Discussionmentioning
confidence: 93%
“…26 This could be due to different accuracy of the imaging technique, different anatomy of the samples or the young age of the patients in this study (the patients did not have enough time to develop changes in the condylar position). 26 Some researchers believe that the reasons for the posterior condylar position arise from disk displacement, 13 osteoarthritis, 23 bone remodeling of the articular eminence and the condyle, 27 and osteoarthrosis. 28 One MRI study revealed that the posterior condyle position was the main feature of TMJ with slight and moderate anterior disk displacement.…”
Section: Discussionmentioning
confidence: 93%
“…[9][10][11] Nonconcentric condyle-fossa relationships have been associated with abnormal TMJ function. 10,[12][13][14][15][16][17][18] However, in other studies, 4,5,13,[19][20][21][22] the presence or absence of temporomandibular disorder (TMD) did not correlate with the condyle position in the TMJ.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has noted the influence of occlusion in the condylar process-mandibular fossa relationship, 4,5,10,[13][14][15][27][28][29][30][31][32][33] while others have not. 4,5,13,[19][20][21][22] Studies have found that the condyles were positioned more anteriorly, 4,5,10,[13][14][15]27,28 posteriorly, 27,29,30 intermediately, 27 superiorly 27,28,31,32 and inferiorly 33 in various occlusal, skeletal, and facial relationships. In addition to condylar position, occlusion might be related to the articular eminence angle or slope 13,14,28 and articular eminence height, 14,16,17 or the vertical height of the fossa 13,19,28,31 and anteroposterior and mediolateral thickness of the condylar head.…”
Section: Introductionmentioning
confidence: 99%